Fractional ac Josephson effect in unconventional superconductors: Сверхпроводимость и мезоскопические структуры - Kwon, Hyok-Jon; Sengupta, K.; Yakovenko, Victor M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
For certain orientations of Josephson junctions between two px-wave or two d-wave superconductors, the subgap Andreev bound states produce a 4p-periodic relation between the Josephson current I and the phase difference j: I µ sin( j/2) . Consequently, the ac Josephson current has the fractional frequency eV/ħ where V is the dc voltage. In the tunneling limit, the Josephson currentis proportional to the first power (not square) of the electron tunneling amplitude. Thus, the Josephson current between unconventional superconductors is carried by single electrons, rather than by Cooper pairs. The fractional ac Josephson effect can be observed experimentally by measuringfrequency spectrum of microwave radiation from the junction.